A new apparatus for measuring elastic wave velocity and electrical conductivity of fluid‐saturated rocks at various confining and pore‐fluid pressures. Issue 3 (15th July 2013) - Watanabe, T.; Higuchi, A.
Abstract Pore‐fluid pressure is a critical parameter that governs geodynamic processes including seismic activities. Its evaluation through geophysical observations provides us insights into these processes. The quantitative evaluation requires a thorough understanding of the influence of pore‐fluid pressure on geophysical parameters, such as seismic velocity and electrical conductivity. To study the influence of pore‐fluid pressure on these parameters, we have built a new apparatus with a pore‐fluid pressure control system, which is capable of simultaneously measuring elastic wave velocity and electrical conductivity. Our new apparatus employs two sets of plastic piston–cylinders for the electrical insulation and pore‐fluid pressure transmission. The pore fluid is electrically isolated from the metal work, and its pressure can be precisely controlled without significant contribution of the friction between the piston and cylinder. Our new apparatus was used for a simultaneous measurement of velocity and conductivity in a brine‐saturated Berea sandstone. Elastic wave velocity and electrical conductivity changed in response to the change in confining and pore‐fluid pressures, showing the usefulness of the new apparatus.